Intelligent Distributed Computing IX Proceedings of the 9th International Symposium on Intelligent Distributed Computing - IDC'2015, Guimarães, Portugal, October 2015 - Novais, Paulo; Camacho, David; Analide, Cesar; El Fallah Seghrouchni, Amal; Badica, Costin (Studies in Computational Intelligence,, 2016)
This book represents the combined peer-reviewed proceedings of the ninth International Symposium on Intelligent Distributed Computing - IDC'2015, of the Workshop on Cyber Security and Resilience of Large-Scale Systems - WSRL'2015, and of the International Workshop on Future Internet and Smart Networks - FI&SN'2015. All the events were held in Guimarães, Portugal during October 7th-9th, 2015. The 46 contributions published in this book address many topics related to theory and applications of intelligent distributed computing, including: Intelligent Distributed Agent-Based Systems, Ambient Intelligence and Social Networks, Computational Sustainability, Intelligent Distributed Knowledge Representation and Processing, Smart Networks, Networked Intelligence and Intelligent Distributed Applications, amongst others.